Qaulan Sadida as A Qur'anic Framework For Revitalizing Character Building in the Digital Era - Hulawa, Djeprin E.; Kasmiati, Kasmiati (Fitrah: Journal of Islamic Education, 2025)
The digital era offers vast benefits but simultaneously brings challenges such as the spread of hoaxes, the degradation of communication ethics, and the moral crisis among younger generations. The Qur'anic concept of Qaulan Sadida, which signifies truthful, just, and responsible speech, is highly relevant in addressing these issues. This study, employing the thematic exegesis method of Abdul Hayy al-Farmawi, analyzes the meaning of Qaulan Sadida in Qur'an Surah An-Nisa: 9 and Qur'an Surah Al-Ahzab: 70, along with the interpretations of exegetes such as Ibn Kathir, Al-Maraghi, and Al-Qurtubi, who emphasize its social-ethical dimensions and self-restraint. Quraish Shihab further highlights its universal nature, making it applicable to da'wah, education, and social interaction. The findings reveal that Qaulan Sadida encompasses five core principles: honesty, gentleness, beneficial speech, justice, and humility. These values are essential in countering hate speech, information manipulation, and the crisis of digital civility. Revitalizing Qaulan Sadida entails fostering ethical, wise, and courteous communication within digital spaces. Islamic educational institutions play a strategic role in this process by integrating these Qur'anic values into curricula, digital literacy programs, and academic culture, thereby nurturing a Muslim generation that is not only digitally literate but also firmly grounded in Qur'anic character.